221k views
20 votes
Please answer this thank you​

Please answer this thank you​-example-1

1 Answer

2 votes

Answer:

x = 0,-1,-2,1,2

y = -3,-5,-7,-1,1

(0,-3)

(-1,-5)

(-2,-7)

(1,-1)

(2,1)

Explanation:

y = 2x - 3

x = 0,-1,-2,1,2

y = ?,?,?,?,?

x = 0

y = 2x - 3

y = 2(0) - 3

y = 0 - 3

y = -3

x = -1

y = 2x - 3

y = 2(-1) - 3

y = -2 - 3

y = -5

x = -2

y = 2x - 3

y = 2(-2) - 3

y = -4 - 3

y = -7

x = 1

y = 2x - 3

y = 2(1) - 3

y = 2 - 3

y = -1

x = 2

y = 2x - 3

y = 2(2) - 3

y = 4 - 3

y = 1

Check:

x = 0,-1,-2,1,2

y = -3,-5,-7,-1,1

(0,-3)

(-1,-5)

(-2,-7)

(1,-1)

(2,1)

Please answer this thank you​-example-1
User Harry Vangberg
by
4.9k points